Migration Law of the Commonwealth of Independent States - Beliakova, Katsiaryna (University of Wroclaw. Faculty of Law, Administration & Economics, 2020)
The article presents multilateral agreements and acts of model legislation constituting the basis of developing migration law in the Commonwealth of Independent States (CIS). The author provides brief characteristics to the acts regulating cooperation in governing migration processes and the status of various types of migrants (both voluntary and forced), as well as model legislation designed to help unify and harmonize the legislation of the CIS member States in the relevant field. The results of the research show that the development of migration law in the CIS continues along the path of convergence with generally accepted norms and standards of international law, clarification of terminology, as well as systematization of model norms. At the same time, the implementation of the adopted norms remains problematic due to the lack of appropriate control mechanisms, as well as sanctions for non-compliance with these norms. In addition, the CIS maintains a special approach to countering illegal migration, which shows the priority of state security issues over the protection of human rights and this is also reflected in the terminology used.The results of research may be used in comparative legal studies of migration law norms in regional legal systems.
Keywords: migracja; prawo migracyjne; modelowy akt ustawodawczy; rekomendacje; emigrant; uchodźca; osoba wysiedlona; pracownik migracyjny